PTU-029 Managing the long-term care of inflammatory bowel disease patients: the cost to European health care providers. (23rd September 2015) - Buchanan, J; Wordsworth, S; Taylor, J; Jewell, D
Abstract : Introduction: Inflammatory Bowel Disease (IBD), which includes Crohn's disease (CD) and Ulcerative Colitis (UC), is a chronic condition characterised by substantial morbidity. Patients with IBD are considered expensive to manage although their use of health care resources has not been sufficiently estimated. To date, few studies have quantified the total cost of caring for IBD patients, preferring to focus on the cost-effectiveness of specific treatments instead. Estimating the resources used and costs incurred when caring for IBD patients is crucial to help healthcare providers plan patient clinical management. This need intensifies with advances in biological therapies and genetic diagnostic tools such as microarrays. Our study developed a framework to estimate the total cost of caring for IBD patients. This framework allows both the estimation of the costs of current care pathways in various settings, and the economic analysis of proposed future interventions. We apply the framework to consider the cost of care for UC and CD patients in the UK and mainland Europe. Methods: Decision models were built to simulate the natural disease history of UC and CD based on clinical pathways mapped in four European hospitals. A healthcare provider perspective was adopted and model inputs applied from published sources and expert opinion. Two hypothetical cohorts of 10 000 UC/CD patients presenting with symptoms of varying severity were modelled over a 10-year period. The average starting age ranged from 25 to 85 years and the models were adjusted to capture differences in clinical management across Europe. Healthcare cost data (test, treatment, surgery, consultation costs) were taken from UK sources and expressed in 2008 prices. Results: The average cost of care over the entire 10-year period for a 45-year-old UC/CD patient was £8035/£7759 in the UK and £7657/£9546 in mainland Europe. These costs are comparable with previous estimates. The average cost per patient fell with patient age. Much of the clinical course for both patient groups was spent in remission, and most costs were incurred soon after diagnosis. The costs of surgery, azathioprine and hospital admission had the greatest effect on the results. Conclusion: Our study confirms that IBD patients are expensive to manage and illustrates the importance of differentiating between alternative clinical management scenarios. The framework we develop is an informative analytical tool which allows healthcare providers to predict the resources required and costs incurred from treating both current and future IBD patients. We acknowledge EC financial support and assistance received from members of the IBDchip consortium.